Bali Beef Quality after the Application of Liquid Smoke in Feed Block during Fattening - Abustam, Effendi; Irfan Said, Muhammad; N. Nahariah, Muhammad Yusuf (European Journal of Sustainable Development, 2019)
The use of liquid smoke as an antioxidant and binder in beef was done in the form of community empowerment in the Cattle Breeders Group in District of Tanete Riaja. The activity aimed to improving the skills of cattle breeder groups in the application of technology in livestock, especially the use of liquid smoke in animal feed. The feed was the primary need for livestock which in certain seasons faced difficulties in providing it. The implementation method was in the application of feed products in the form of urea water coconut liquid-smoke multi-nutrient block (UCSMB). Three concentrations of liquid smoke were added to the feed, namely 0, 10 and 20%. The production of probiotic fermented rice straw was carried out as a source of fiber to complete feed entirely. The application of feed products was carried out on 12 male Bali beef aged 2-3 years for 45 days. After the cattle were slaughtered, the Longissimus dorsi dissection muscle was then aged for 0, 7 and 14 days. The parameters of meat quality were pH, water holding capacity (WHC), shear force of meat cooked value, and cooking loss. The results showed that meat quality increased with increasing concentration and aging time. Keywords: Bali beef, fermented straw, liquid smoke, meat quality, UCSMB